John Ericsson papers - Ericsson, John, 1803-1889.
Correspondence, writings, design specifications, articles, memoranda, technical notes, financial and legal papers, drawings, printed matter, and miscellany relating primarily to Ericsson's activities in marine engineering, especially his work on screw propellers and his design of the steamship Princeton and the ironclad Monitor. Includes material pertaining to his work with Destroyer warships used in anti-submarine warfare, solar energy, the pyrometer, the hydrometer, gun installations, floating batteries, revolving turrets, development of fleets, and outfitting of ships of war. Also includes correspondence of Ericsson's biographer, William Conant Church.
Ericsson's correspondents include A. Adlersparre, S. B. Browning, William E. Chandler, John Adolphus Bernard Dahlgren, Cornelius Henry Delamater, Hjalmar Elworth, Nils Ericson, Gustavus Vasa Fox, John A. Griswold, Charles H. Haswell, Eben Norton Horsford, Robert Green Ingersoll, William Gore Jones, Francis Barber Ogden, Oscar II, King of Sweden, Epes Sargent, John Osborne Sargent, William Henry Seward, Joseph Smith, Robert Field Stockton, and Gideon Welles.
Microfilm edition of a portion of the papers is also available
Microfilm produced from originals in the Manuscript Division.
Library of Congress Prints and Photographs Division.
Swedish-born engineer and inventor; emigrated to the United States in 1839.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Adlersparre, A. -- Correspondence; Browning, S. B. -- Correspondence; Chandler, William E. -- 1835-1917 -- Correspondence; Church, William Conant, -- 1836-1917 -- Correspondence; Dahlgren, John Adolphus Bernard, -- 1809-1870 -- Correspondence; Delamater, Cornelius Henry, -- 1821-1899 -- Correspondence; Elworth, Hjalmar -- Correspondence; Ericson, Nils -- Correspondence; Fox, Gustavus Vasa, -- 1821-1883 -- Correspondence; Griswold, John A. -- 1818-1872 -- Correspondence; Haswell, Chas. H. -- 1809-1907 -- Correspondence; Horsford, Eben Norton, -- 1818-1893 -- Correspondence; Ingersoll, Robert Green, -- 1833-1899 -- Correspondence; Jones, William Gore -- Correspondence; Ogden, Francis Barber, -- 1783-1857 -- Correspondence; Oscar -- II, -- King of Sweden, -- 1829-1907 -- Correspondence; Paulding, Hiram, -- 1797-1878 -- Correspondence; Sargent, Epes, -- 1813-1880 -- Correspondence; Sargent, John Osborne, -- 1811-1891 -- Correspondence; Seward, William Henry, -- 1801-1872 -- Correspondence; Smith, Joseph, -- 1790-1877 -- Correspondence; Stockton, Robert Field, -- 1795-1866 -- Correspondence; Welles, Gideon, -- 1802-1878 -- Correspondence; United States. -- Navy -- History -- 19th century; Monitor (Ironclad); Princeton (Steamship); Anti-submarine warfare; Armored vessels; Destroyers (Warships); Floating batteries; Hydrometer; Marine engineering; Naval architecture; Ordnance, Naval; Propellers; Pyrometers; Shipbuilding; Solar energy; Warships; Warships -- Turrets; United States -- History, Naval -- 19th century; Engineers; Inventors